2013
DOI: 10.5846/stxb201111251801
|View full text |Cite
|
Sign up to set email alerts
|

A study of meiofauna in the COMRA's contracted area during the summer of 2005

Abstract: Polymetallic nodules were discovered on the Pacific Ocean in 1891. They exist at the sediment surface, sometimes in upper layers of sediments, and cover more than 50% of the sea floor at Clarion鄄Clipperton fracture Zone ( CCFZ) in the north Pacific. The huge economic value from nodule mining has brought to many research programs dedicated to resource evaluation and design of collecting tools in the 1970s. China has carried out surveys on polymetallic nodules and sediment in the CCFZ for many years. Since the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Similar to other studies in the CCFZ (Wilson & Hessler, 1987;Kaneko et al, 1997;Radziejewska & Modlitba, 1999;Kim et al, 2000;Gao et al, 2002;Min et al, 2004;Kim et al, 2004;Wang et al, 2013;Min et al, 2018), elsewhere in the Pacific Ocean (e.g., Snider et al, 1984;Shirayama, 1984) and other oceans worldwide (e.g., Ansari & Parulekar, 1981;Woods & Tietjen, 1985;Shirayama & Kojima, 1994;Zeng et al, 2018), the majority of meiobenthos are concentrated in the top sediment layers. Meiofaunal higher taxon composition (including "Nauplii") was also similar, in J o u r n a l P r e -p r o o f that the Nematoda was the most prevalent, or Foraminifera if the study included the protozoans, followed by the Nauplii and Copepoda (Wilson & Hessler, 1987;Kaneko et al, 1997;Radziejewska et al, 2001;Kim et al, 2000;Gao et al, 2002;Kim et al, 2004;Min et al, 2004;Wang et al, 2013;Pape et al, 2017;Min et al, 2018;Hauquier et al, 2019).…”
Section: Name Of Expeditionsupporting
confidence: 84%
“…Similar to other studies in the CCFZ (Wilson & Hessler, 1987;Kaneko et al, 1997;Radziejewska & Modlitba, 1999;Kim et al, 2000;Gao et al, 2002;Min et al, 2004;Kim et al, 2004;Wang et al, 2013;Min et al, 2018), elsewhere in the Pacific Ocean (e.g., Snider et al, 1984;Shirayama, 1984) and other oceans worldwide (e.g., Ansari & Parulekar, 1981;Woods & Tietjen, 1985;Shirayama & Kojima, 1994;Zeng et al, 2018), the majority of meiobenthos are concentrated in the top sediment layers. Meiofaunal higher taxon composition (including "Nauplii") was also similar, in J o u r n a l P r e -p r o o f that the Nematoda was the most prevalent, or Foraminifera if the study included the protozoans, followed by the Nauplii and Copepoda (Wilson & Hessler, 1987;Kaneko et al, 1997;Radziejewska et al, 2001;Kim et al, 2000;Gao et al, 2002;Kim et al, 2004;Min et al, 2004;Wang et al, 2013;Pape et al, 2017;Min et al, 2018;Hauquier et al, 2019).…”
Section: Name Of Expeditionsupporting
confidence: 84%
“…Gao et al (2002), Yang et al (2005), and Liu et al (2014) studied the abundance, biomass, and spatial distribution of meiofauna. Ye et al (2005) and Wang et al (2013) studied the methodology of meiofauna research in deep sea. Although deep seas are less disturbed by humans than shallow waters, deep-sea ecosystems are disrupted as mineral extraction, natural gas/hydrocarbon exploration and global warming, ocean acidification, hypoxia, etc.…”
Section: Introductionmentioning
confidence: 99%
“…was the most relatively abundant species at Station S1 (27.6%) (Table 5). This study showed that the marine tardigrade abundance in the deep South China Sea was much higher than that in the abyssal East Pacific Ocean and the adjacent areas to the Yap Trench of the Western Pacific Ocean (Table 6) (Wang et al, 2013;Wang et al, 2019). Many studies have indicated that food availability is an important factor that affects meiofauna abundance (Danovaro et al, 2002;Gambi and Danovaro, 2016;Leduc et al, 2016).…”
Section: Similarity Analysismentioning
confidence: 73%